Accelerating change in schools : leading rapid, successful, and complex change initiatives - Dudar, Linda; Scott, Shelleyann; Scott, Donald E. (Advances in educational administration, 2017)
This book presents major findings from a research study exploring the leadership needed to enact rapid change - defined as three years or less - in various school contexts, overtly including the perspectives of leaders, teachers, students, parents, community members, and district leaders.